Methods of optimizing the radiation dose during computed tomography - Alkhanova, A.; Zhumadilov, K.; Dautov, T.; Abdykalyk, Galymzhan (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
Computed tomography is the most effective method of radiation diagnosis. Starting from computed tomography, the optimization principle should be used to keep radiation doses to patients at an acceptable level. An integral part of optimization is the search for a compass between reducing the patients dose and obtaining an acceptable quality image with reliable diagnostic information. The parameters of the computed tomography are determined by the patient’s radiation dose and the quality of the diagnostic image. The purpose of the article is it radiation exposure to patients. For the same reason, we considered tube current modulation. This method reduces radiation without changing the quality of the image and noise.